2019
DOI: 10.1111/dme.13957
|View full text |Cite
|
Sign up to set email alerts
|

Altered accelerator pedal control in a driving simulator in people with diabetic peripheral neuropathy

Abstract: Aim To investigate whether the sensory-motor impairment attributable to diabetic peripheral neuropathy would affect control of the accelerator pedal during a driving simulator task.Methods A total of 32 active drivers, 11 with diabetic peripheral neuropathy (mean AE SD age 67AE5.0 years), 10 with diabetes but no neuropathy (diabetes group; mean AE SD age 62AE10 years), and 11 healthy individuals without diabetes (healthy group; mean AE SD age 60AE11 years), undertook a test on a dynamometer to assess ankle pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Patients with DPN and prior lower-extremity amputations have a 50% higher risk for losing a second limb within the next 2 years and 5-year survival rates that are substantially lower than age-and sexmatched patients with diabetes without DPN (1)(2)(3). DPN has multiple other consequences, such as major impact on impaired daily function through small-and large-nerve fiber dysfunction, as well as loss of sensory perception, including proprioception, temperature discrimination, and pain, all of which ultimately lead to unsteadiness; recurrent minor injuries, with an increased risk of falls and fractures (1,4); impact on daily function (1,4); impaired control of the accelerator pedal while driving (5); poor oral health (6); and poor quality of life (1,7). Thus, the clinical and socioeconomic costs of DPN are staggering.…”
mentioning
confidence: 99%
“…Patients with DPN and prior lower-extremity amputations have a 50% higher risk for losing a second limb within the next 2 years and 5-year survival rates that are substantially lower than age-and sexmatched patients with diabetes without DPN (1)(2)(3). DPN has multiple other consequences, such as major impact on impaired daily function through small-and large-nerve fiber dysfunction, as well as loss of sensory perception, including proprioception, temperature discrimination, and pain, all of which ultimately lead to unsteadiness; recurrent minor injuries, with an increased risk of falls and fractures (1,4); impact on daily function (1,4); impaired control of the accelerator pedal while driving (5); poor oral health (6); and poor quality of life (1,7). Thus, the clinical and socioeconomic costs of DPN are staggering.…”
mentioning
confidence: 99%
“…As a result of reduced muscle strength, Restrictions in the neck, shoulder, and wrist movements can limit vision and the ability to control the steering wheel. Sensory and/or motor neuropathy is common in older adults and may impair brake and accelerator pedal use [43].…”
Section: Discusssionmentioning
confidence: 99%
“…In addition, the road traffic crash rate is largely influenced by young people, particularly male drivers, a population in which the prevalence of diabetes is considerably lower than in older age groups [ 7 ]. Nonetheless, simulation studies have clearly demonstrated that people with diabetes tend to exhibit poor performance in muscle functioning, ankle proprioception, and accelerator pedal control [ 8 ]. Moreover, a study found that compared to individuals without diabetes who had equal confidence in their driving skills, patients with type 2 diabetes exhibited worse driving performance, as evidenced by a larger centerline deviation, a longer brake reaction time, and a shorter minimum time to collision [ 9 ].…”
Section: Introductionmentioning
confidence: 99%